Predicting Santri Engagement by Attachment to Caregiver - Ridho, Ali (Jurnal Online Psikogenesis, 2024)
This study explores the predictive relationship between santri (students in Islamic boarding schools, pesantren) engagement and their attachment to caregivers. Drawing upon a sample of 99 santris (65 males and 34 females) from a boarding school for students aged 10 to 20 years (M = 15.75, SD = 2.16), this research employs convenience sampling and sophisticated questionnaire analysis. Applying the graded response model (GRM) for calibration, the study precisely estimated the santris' scale scores of engagement and attachment, which were subsequently analyzed through regression to examine the predictive capacity of attachment to caregiver on student engagement. Results indicated a significant relationship (b = 0.43, p < 0.01), emphasizing the importance of attachment to caregivers in predicting santri engagement within the pesantren context. The application of GRM enhanced the precision of scaling attachment and engagement. It bolstered the regression analysis's validity, confirming the hypothesis that caregiver attachment can reliably predict student engagement in boarding school settings.